Topical steroid-damaged skin - Anil Abraham; Gillian Roga (Wolters Kluwer Medknow Publications, 2014)
Topical steroids, commonly used for a wide range of skin disorders, are associated with side effects both systemic and cutaneous. This article aims at bringing awareness among practitioners, about the cutaneous side effects of easily available, over the counter, topical steroids. This makes it important for us as dermatologists to weigh the usefulness of topical steroids versus their side effects, and to make an informed decision regarding their use in each individual based on other factors such as age, site involved and type of skin disorder.